2009
DOI: 10.1262/jrd.20026
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment with Bromocriptine Inhibits Endometrial Adenocarcinoma Development in Rats

Abstract: Abstract. The effects of long-term blockade of prolactin (PRL) action by bromocriptine (BRC) treatment on uterine carcinogenesis and on related ovarian physiology were investigated using a rat uterine cancer model. Ten-week-old cycling female Donryu rats, a high yield strain for uterine corpus tumors (endometrial adenocarcinomas), were treated with N-ethyl-N'-nitro-N-nitrosoguanidine (ENNG), as a tumor initiator, and injected with 1 mg/kg body weight BRC subcutaneously 4 times per week until 14.5 months of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Examination of the long‐term effects of sulpiride or EGME on uterine carcinogenicity was performed modifying the Donryu rat initiation–promotion assay model for uterine corpus cancer (Ando‐Lu et al, ; Yoshida et al, ). Briefly, at 10 weeks of age, all female pups were administered a single dose of 20 mg kg −1 ENNG into the uterine horn using a stainless steel catheter via the vagina.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the long‐term effects of sulpiride or EGME on uterine carcinogenicity was performed modifying the Donryu rat initiation–promotion assay model for uterine corpus cancer (Ando‐Lu et al, ; Yoshida et al, ). Briefly, at 10 weeks of age, all female pups were administered a single dose of 20 mg kg −1 ENNG into the uterine horn using a stainless steel catheter via the vagina.…”
Section: Methodsmentioning
confidence: 99%
“…Aged Donryu rats exhibit a high incidence of spontaneous uterine endometrial adenocarcinomas, which are similar to human cases as follows: (1) multistep development of uterine lesions from atypical hyperplasias to adenocarcinomas; (2) ovarian hormonal imbalance, in particular, elevation of the serum E 2 level relative to P4; and (3) morphologic similarities to endometrioid adenocarcinomas in humans (Maekawa et al, ). Thus, Donryu rats are a useful model for assessing endometrial adenocarcinoma in the corpus in women, particularly for endometrioid adenocarcinoma (Yoshida et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Donryu rats have been historically used for the investigation of EC etiology and they helped to elucidate that hormonal imbalance, more specifically an increased estrogen:progesterone (E:P) ratio, can be linked to EC development [76,77]. Yoshida et al and Kojima et al showed that compounds decreasing the E:P ratio, such as bromocriptine and indole-3-carbinole, have a protective effect against EC [77,78], while compounds increasing the E:P ratio have the opposite effect.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…Yoshida et al and Kojima et al showed that compounds decreasing the E:P ratio, such as bromocriptine and indole-3-carbinole, have a protective effect against EC [77,78], while compounds increasing the E:P ratio have the opposite effect. These observations explain why neonatal exposure to a high dose of the estrogenic compound p-t-octylphenol increases the likelihood of EC development [79].…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…GBR12909), have been shown clinically to reduce prolactin levels and induce central‐mediated side effects such as nausea, vomiting, headache and hallucination . D2 receptor agonists, such as bromocriptine, are the treatment of choice for the majority of patients suffering from hyperprolactinaemia and prolactinoma; if given chronically, these agents can increase incidences of prolactin‐sensitive tumours in rats , but not in human beings .…”
mentioning
confidence: 99%